Economic constraints and gendered rules: Understanding women’s perspectives of how government-imposed restrictions impact women’s mental health and social wellbeing across Afghanistan - Lyla Schwartz; Zainab Hassanpoor; Hannah Lane; Elizabeth Klapheke (SSM - Mental Health)
This paper examines how the mental health and participation in work-related and social activities of women in Afghanistan has been impacted by the socio-political changes that have been enforced since August 2021. The study hypothesizes that women across Afghanistan from diverse sectors, both formal and informal, are negatively affected by the imposed restrictions, and that it impacts their participation in the workforce, their mental health, and their overall living conditions. The analysis within this paper is based on 124 Key Informative Interviews (KIIs) and Focus Group Discussions (FGDs), which included 33 men and 154 women across six geographic regions of Afghanistan. The findings suggest that within formal and informal job sectors, women have felt a significant disconnect from the market and the community in which they were once thriving, and as a result have experienced worsened living conditions and diminished social status. The paper discusses the significance of women’s participation in the workforce and the positive and meaningful impact women can bring to their communities; highlighting women’s frustration and documenting firsthand accounts of women’s experiences in this new socio-political landscape. It also highlights the new initiatives women are undertaking to continue their work and engage in social activities.